2017
DOI: 10.1155/2017/8546192
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding Practice and Associated Factors among Mothers Attending Private Pediatric and Child Clinics, Addis Ababa, Ethiopia: A Cross-Sectional Study

Abstract: Background The prevalence of exclusive breastfeeding (EBF) is globally low (35%) in sub-Saharan Africa, whereas it is 58% in Ethiopia. Exclusive breastfeeding has the potential to prevent 11.6% of under-five deaths in developing countries. Therefore, the main objective of this study was to assess the exclusive breastfeeding practice and associated factors on mothers attending private pediatric and child clinics in Addis Ababa, Ethiopia. Methods An institutional-based cross-sectional study design was used. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 20 publications
9
44
2
4
Order By: Relevance
“…Twelve of the studies were from Amhara [34][35][36][37][38][39][40][41][42][43]55,68], two from Addis Ababa [52,53], three from Affar [33,58,63], three from Oromia [45,64,65], twelve from SNNP [46][47][48]51,52,54,57,59,60,61,62,66], one from Tigray [67], one from Somalia [49],one from Harari [44]and one from nationwide [50]. No studies reported from Benishangul Gumiz,Gagmbela and Dire dawa council city in this review research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve of the studies were from Amhara [34][35][36][37][38][39][40][41][42][43]55,68], two from Addis Ababa [52,53], three from Affar [33,58,63], three from Oromia [45,64,65], twelve from SNNP [46][47][48]51,52,54,57,59,60,61,62,66], one from Tigray [67], one from Somalia [49],one from Harari [44]and one from nationwide [50]. No studies reported from Benishangul Gumiz,Gagmbela and Dire dawa council city in this review research.…”
Section: Resultsmentioning
confidence: 99%
“…Maternal employment [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50],Mode of delivery [34,39,41,42,43,45,[50][51][52][53][54],Marital status [33,34,41,42,47,55,56,57],colostrum feeding [35,37,38,43,58,59,60,61],prelacteal feeding [ 34,38,43,55,57,62],age of mother…”
Section: Introductionmentioning
confidence: 99%
“…9 Conversely, according to Elyas et al, a study conducted in rural China reported that mothers with an education level above senior middle school were less likely to breastfeed their infants exclusively. 15 Also, the findings showed that most of those mothers were working and living with their husbands.…”
Section: Discussionmentioning
confidence: 97%
“…According to the definition the World Health Organization (WHO), Exclusive breastfeeding (EBF) is the situation in which an infant receives only breast milk from his/her mother or a wet nurse for the first 6 months and no other solids or liquids with the exception of drops or syrups consisting of vitamins, minerals, supplements, or medicines [1].…”
Section: Introductionmentioning
confidence: 99%